Purificação de duas novas lectinas de Leguminosae: Collaea speciosa (Loisel.) DC. (subfamília Papilonoideae; tribo Phaseoleae) e Vataireopsis araroba (Aguiar) Ducke (subfamília Papilonoideae; tribo Dalbergieae) - Oliveira, Messias Vital de (2022)
Abundantly present in living beings, the largest group of lectins ever researched are from plants. Differences in molecular structures, biochemical properties and carbohydrate-binding specificities can be noted between them. Through these characteristics, there are ways of classifying this heterogeneous group of lectins as their organization in families, which is defined by the sequence of amino acids in the lectin domain. All proteins composed of one or more lectin domains, combined or not with other domains of similar or different activity, can be defined as lectins. The distribution of these molecules occurs in different cellular compartments and, depending on their location, they can find a wide variety of carbohydrate structures, thus allowing them to be involved in multiple biological functions. Historically, studies on the carbohydrate-binding properties of these proteins have resulted in several potentially viable applications: therapeutic agents, (immune)histochemical markers, biomarkers, affinity chromatography, probes, and microarrays, among others. These applications increasingly motivate the search for new lectins with properties that guarantee their applicability in techniques that are economically viable and more competitive. In this sense, we present two new lectins belonging to the species Collaea speciosa (CsL) and Vataireopsis araroba (VaL), the first genera, belonging to the tribe Phaseoleae and Dalbergieae respectively. Each lectin was purified in only one type of affinity chromatography and exhibited more specificity for GlcNAc (CsL) and GalNAc (VaL). Their physicochemical characterization profiles were similar to those of Leguminosae lectins, but some peculiarities were noted in CsL such as their specificity, thermostability and amino acid sequence partially different from the other lectins that make up the Diocleinae subtribe, which leads us to believe that this lectin may be the first of a new group within the lectins that constitute this taxon. Another highlight was observed in Val, where the cytotoxicity tests with insect cells showed a biostatic effect by reducing cell growth. Notably, there was cell agglutination, a typical phenomenon that occurs between the lectin and cell surface glycans. However, further studies of structural characterization and biological activity are needed to validate the data presented for both lectins.